2014
DOI: 10.1002/2013jd021357
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crop residue burning on aerosol properties, plume characteristics, and long‐range transport over northern India

Abstract: Aerosol emissions from biomass burning are of specific interest over the globe due to their strong radiative impacts and climate implications. The present study examines the impact of paddy crop residue burning over northern India during the postmonsoon (October-November) season of 2012 on modification of aerosol properties, as well as the long-range transport of smoke plumes, altitude characteristics, and affected areas via the synergy of ground-based measurements and satellite observations. During this perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
131
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(145 citation statements)
references
References 114 publications
(203 reference statements)
13
131
1
Order By: Relevance
“…The mean specific conductivity over IGP region is much higher than that reported by IMD (1982) in rainwater at 10 background locations in India (5-57 µS cm -1 ). Prior studies (Ghude et al, 2008;Srivastava et al, 2012;Tiwari et al, 2013;Kaskaoutis et al, 2014; http://www.moef.nic.in, and references therein) of the atmospheric aerosol over the IGP region indicated high concentrations of fine particles produced by man-made and natural sources.…”
Section: Variability Of Ph and Specific Conductivitymentioning
confidence: 99%
“…The mean specific conductivity over IGP region is much higher than that reported by IMD (1982) in rainwater at 10 background locations in India (5-57 µS cm -1 ). Prior studies (Ghude et al, 2008;Srivastava et al, 2012;Tiwari et al, 2013;Kaskaoutis et al, 2014; http://www.moef.nic.in, and references therein) of the atmospheric aerosol over the IGP region indicated high concentrations of fine particles produced by man-made and natural sources.…”
Section: Variability Of Ph and Specific Conductivitymentioning
confidence: 99%
“…Nainital) will continued to be exposed to the regional sources and hence the M BC levels continue to be high till the spring months. Earlier studies also have shown the influence of transported plumes originating from crop residue burning in the northwest India over the Himalayan sites 17,43,44,47 . Kaskaoutis et al 44 attributed the high aerosol loading observed over the eastern Himalaya during post-monsoon to the possible transport of plumes originated from crop residue and biomass burning activities over the western IGP (mainly Punjab).…”
Section: Role Of Transport From Source Regionsmentioning
confidence: 92%
“…Earlier studies also have shown the influence of transported plumes originating from crop residue burning in the northwest India over the Himalayan sites 17,43,44,47 . Kaskaoutis et al 44 attributed the high aerosol loading observed over the eastern Himalaya during post-monsoon to the possible transport of plumes originated from crop residue and biomass burning activities over the western IGP (mainly Punjab). By November, the winter conditions (sub-zero temperatures and appearance of snow caps on the mountain peaks) set in, with shallow local ABL keeping the pollutants close to the surface and with the mountain peaks being above this local ABL, BC level decreases in November.…”
Section: Role Of Transport From Source Regionsmentioning
confidence: 92%
See 1 more Smart Citation
“…This is strongly possible as agricultural residue burning is prevalent in these regions (e.g., Kaskaoutis et al, 2014;Vadrevu et al, 2015). Over India and over Southeast Asia, our ER (HCOOH/CO) values (6.8 × 10 −3 ± 0.44 × 10 −3 mol mol −1 for India and 5.8 × 10 −3 ± 0.15 × 10 −3 mol mol −1 for Southeast Asia) are close to the value referenced by Akagi et al (2011) for cropland fires (6 × 10 −3 mol mol −1 ).…”
Section: Analysis Based On the Type Of Vegetationmentioning
confidence: 99%